Surface ocean warming near the core of hurricane Sam and its representation in forecast models - Andrew M. Chiodi; Andrew M. Chiodi; Hristina Hristova; Hristina Hristova; Gregory R. Foltz; Jun A. Zhang; Jun A. Zhang; Calvin W. Mordy; Calvin W. Mordy; Catherine R. Edwards; Chidong Zhang; Christian Meinig; et al. (Frontiers in Marine Science, 2024)
On September 30, 2021, a saildrone uncrewed surface vehicle intercepted Hurricane Sam in the northwestern tropical Atlantic and provided continuous observations near the eyewall. Measured surface ocean temperature unexpectedly increased during the first half of the storm. Saildrone current shear and upper-ocean structure from the nearest Argo profiles show an initial trapping of wind momentum by a strong halocline in the upper 30 m, followed by deeper mixing and entrainment of warmer subsurface water into the mixed layer. The ocean initial conditions provided to operational forecast models failed to capture the observed upper-ocean structure. The forecast models failed to simulate the warming and developed a surface cold bias of ~0.5°C by the time peak winds were observed, resulting in a 12-17% underestimation of surface enthalpy flux near the eyewall. Results imply that enhanced upper-ocean observations and, critically, improved assimilation into the hurricane forecast systems, could directly benefit hurricane intensity forecasts.